Redox state‐dependent modulation of plant SnRK1 kinase activity differs from AMPK regulation in animals. Issue 21 (4th October 2017) - Wurzinger, Bernhard; Mair, Andrea; Fischer‐Schrader, Katrin; Nukarinen, Ella; Roustan, Valentin; Weckwerth, Wolfram; Teige, Markus
Abstract : The evolutionarily highly conserved SNF1‐related protein kinase (SnRK1) protein kinase is a metabolic master regulator in plants, balancing the critical energy consumption between growth‐ and stress response‐related metabolic pathways. While the regulation of the mammalian [AMP‐activated protein kinase (AMPK)] and yeast (SNF1) orthologues of SnRK1 is well‐characterised, the regulation of SnRK1 kinase activity in plants is still an open question. Here we report that the activity and T‐loop phosphorylation of AKIN10, the kinase subunit of the SnRK1 complex, is regulated by the redox status. Although this regulation is dependent on a conserved cysteine residue, the underlying mechanism is different to the redox regulation of animal AMPK and has functional implications for the regulation of the kinase complex in plants under stress conditions. Abstract :